A Correlation Analysis among Pain Intensity, Functional Disability and Range of Motion using Low Level Laser Therapy in patients with Discogenic Lumbar Radiculopathy: Correlation among Pain Intensity, Functional Disability and Range of Motion using Low Level Laser - Ahmed, Ishaq; Bandpei, Mohammad Ali Mohseni; Gilani, Syed Amir; Ahmad, Ashfaq; Zaidi, Faryal (Journal of Lasers in Medical Sciences, 2022)
Background: Laser is a pain-free and non-invasive treatment modality. It is used in many acute and chronic painful conditions. In recent times, the use of low intensity laser for physical therapy has been shown to significantly reduce pain with a variety of causes. Objectives: To determine the correlation among pain intensity, functional disability and range of motion using Low Level Laser therapy in patients with Discogenic Lumbar Radiculopathy. Methodology: This cross sectional study was conducted as a part of a randomized controlled trial of Low Level Laser therapy in treating patients with Discogenic Lumbar Radiculopathy at Physical therapy departments of three different hospitals from August 2021 to September 2021. The study was conducted according to STROBE guidelines. Fifty Five (55) patients from experimental group of trial were invited to participate in this study. The outcomes of treatment were recorded on a semi-structured questionnaire on the first day and last day of treatment from each patient’s pain intensity, functional disability and Lumbar range of motion by using Visual Analogue Scale, Oswestry Disability Index, Dual Inclinometer respectively. The data was analyzed through SPSS version 21.0. Results: The results of Correlation Coefficient/ Pearson’s Correlation of VAS, ODI and Dual Inclinometer were varied. The strength of correlation between variables was weak to moderate (r = 0.033 to 0.425) with statistically Insignificant correlation coefficient (P > 0.05, CI 95%) except for Lumbar Flexion (P < 0.05, CI 95%). Conclusions: Weak to moderate correlations were found among pain intensity, functional disability and Lumbar range of motion using Low Level Laser Therapy at a wavelength of 830-nm and a dose of 3 J/point for acute LBP with Discogenic Lumbar Radiculopathy. In addition, no major side effects were observed during and after the use of LLL.